Hippotherapy as a Complementary Intervention for Multiple Sclerosis: A Review - Bryksy, Sylwia; Przybyłowska , Agnieszka; Popczyk, Natalia; Jopek, Jakub; Piechowicz , Agnieszka; Popczyk, Michał; Marciszewska, Aleksandra; Świątecka, Martyna; Kaźmierczyk , Jakub (Quality in Sport, 2025)
Introduction: Multiple sclerosis is a chronic autoimmune disease of the central nervous system (CNS). The pathogenesis of multiple sclerosis is complex and incompletely understood. The major factors that lead to the disease seem to be inflammation and neurodegeneration. Multiple sclerosis is diagnosed by meeting diagnostic criteria. They are based on demonstrating the involvement of 2 or more areas of the CNS at different time points. There remains no cure for multiple sclerosis. Treatment has three aspects: symptom management, relapse management, and disease-modifying therapy. Despite the benefits of pharmacological and non-pharmacological treatments, studies indicate that several complementary therapies may also be promising. One such therapy is hippotherapy, an equine-assisted form of physical therapy that uses the characteristic movements of a horse. Aim of the study: The aim of this study was to review the published literature on the impact of hippotherapy on multiple sclerosis. Materials and methods: A review of available studies examining the relationship between hippotherapy and multiple sclerosis was conducted. To identify relevant literature, the PubMed and Google Scholar databases were used. Results: Several studies investigating the effect of hippotherapy as a complementary intervention on the course of multiple sclerosis indicate that this intervention can be beneficial for affected patients. Patients in the hippotherapy intervention group showed improvements in balance, fatigue, spasticity, walking performance, spatiotemporal gait parameters, processing of sensory cues for postural control, trunk and upper-limb control, dynamic control, facilitated movement, and quality of life. Conclusions: Hippotherapy may be a useful complementary treatment for improving walking and other functional outcomes in people with multiple sclerosis, but the available evidence remains limited and further studies are needed.